Separation, preconcentration, extraction and spectrophotometric determination of Mn(VII) from Acidic Aqueous medium - Fatimah A.Wanns Alghurabi; Shawket K. Jwad (Al-Qadisiyah Journal of Pure Science, 2019)
ABSTRACT: Liquid ion exchange method as sensitive application method of solvent extraction used for separation and determination Mn(VII) as MnO4- from aqueous solution by used P-amino benzoic acid (P-ABA)in presence hydrochloric acid HCl at exact concentration. Spectrophotometric study show wave length for maximum absorbance of ion pair association complex extracted was λMax = 286nm as well as the study about pinpoint the optimum conditions for higher extraction efficiency shows this method need 0.6 MHCl in presence 60µg/5ml of Mn(VII) as MnO4- and shaking time equal to (10min), the study shows extraction method was endothermic and thermodynamic data, was    ∆Hex = 0.1374 kJmol-1   ∆Gex= -60.89 KJ mol-1 ∆Sex = 194.926 Jmol-1 as well as the study involved electrolytes effect, interference effect, organic solvent effect so that spectrophotometric Determination of Mn(VII) in different samples